2019
DOI: 10.3389/fpsyg.2019.02541
|View full text |Cite
|
Sign up to set email alerts
|

Using a Mindfulness-Based Intervention to Promote Subjective Well-Being, Trait Emotional Intelligence, Mental Health, and Resilience in Women With Fibromyalgia

Abstract: The objective of the present study was to experimentally assess the effects of a mindfulness-based intervention (MBI) for the improvement of subjective well-being, trait emotional intelligence (TEI), mental health, and resilience in a sample of women with fibromyalgia (FM). The sample consisted of 104 women, between 29 and 77 years old (M = 47.59; SD = 5.93). The measures used were as follows: Satisfaction with Life Scale (SWLS), Positive and Negative Affection Scale (PANAS), Trait Emotional Intelligence Quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 68 publications
0
22
0
5
Order By: Relevance
“…On the contrary, the total resilience values and the I factor (personal competence) obtained in our sample are higher than those reached in the study carried out by Sánchez-Teruel et al [28] in young healthy people. The case of populations with painful chronic pathologies such as fibromyalgia [35] highlights that our results are much higher (almost double) for this variable. It will be interesting to analyze the role of the associations in the promotion of the health of patients diagnosed with MS.…”
Section: Discussionmentioning
confidence: 54%
“…On the contrary, the total resilience values and the I factor (personal competence) obtained in our sample are higher than those reached in the study carried out by Sánchez-Teruel et al [28] in young healthy people. The case of populations with painful chronic pathologies such as fibromyalgia [35] highlights that our results are much higher (almost double) for this variable. It will be interesting to analyze the role of the associations in the promotion of the health of patients diagnosed with MS.…”
Section: Discussionmentioning
confidence: 54%
“…Prior studies in populations with other conditions including cancer, diabetes, fibromyalgia, and older adults in general have demonstrated that resilience can improve with targeted interventions such as mindfulness and/or cognitive behavioral therapy. [19][20][21][22][23][24] Though research on whether resilience training impacts physiologic health outcomes is limited, improvements in HDL cholesterol, fasting blood glucose, and bodily pain in patients with diabetes and chronic pain have been reported with such interventions. 21,25 Lastly, given the association between resilience and mental health disorders, treatment of mental health disorders may be incorporated into strategies to simultaneously improve resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Second, resilience as a risk factor may be modifiable. Prior studies in populations with other conditions including cancer, diabetes, fibromyalgia, and older adults in general have demonstrated that resilience can improve with targeted interventions such as mindfulness and/or cognitive behavioral therapy 19‐24 . Though research on whether resilience training impacts physiologic health outcomes is limited, improvements in HDL cholesterol, fasting blood glucose, and bodily pain in patients with diabetes and chronic pain have been reported with such interventions 21,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the changes that are reported by parents, one of the most important skills for the exercise of parenting that helps to improve the relationship between parents and children is emotional intelligence [24]. Emotional intelligence could be defined as the emotional competence to manage emotions, feelings, and thoughts; its objective is to enable individuals to interact with their environment in a rational way in order to promote the capacity to adapt to different contexts and situations and build relationships that are satisfying and promote personal growth [25].…”
Section: The Mindfulness-based Stress Reduction Programmentioning
confidence: 99%